ANALISIS KEBIJAKAN KURIKULUM 2013 TERKAIT IMPLEMENTASI PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 - FAUZATUL MA'RUFAH ROHMANURMETA (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
This study aims to determine the 2013 curriculum policy during the COVID-19 pandemic, and the impact of the online learning system applied. The research method used in this research is descriptive qualitative method with analysis techniques. This type of research is carried out in the form of library research. Library research is carried out by observing various literature related to the problem. The result of this study is that the 2013 curriculum policy during the Covid 19 pandemic requires learning to be carried out online with a provision for independent learning. This policy was established to prevent the spread of Covid 19. The implementation of online learning has several obstacles, including the lack of electronic facilities owned by parents of students at the elementary level, and the existence of an internet network that is not smooth. So that the implementation of the 2013 curriculum with online learning is not fully effective to use.